Polycyclic Aromatic Hydrocarbons and Endocrine Disruption: Role of Testicular Gap Junctional Intercellular Communication and Connexins - Kubincová, Petra; Sychrová, Eliška; Raška, Jan; Basu, Amrita; Yawer, Affiefa; Dydowiczová, Aneta; Babica, Pavel; Sovadinová, Iva (Toxicological sciences, 2019)
Ambient air pollution and smoking are well-documented risk factors for male infertility. Prevalent air pollutants and cigarette smoke components, polycyclic aromatic hydrocarbons (PAHs), are environmental and occupational toxicants that act as chemicals disrupting endocrine regulation and reproductive potential in males. Testicular gap junctional intercellular communication (GJIC) is critical for normal development and function of testicular tissue, thus we assessed GJIC as a process potentially targeted by PAHs in testes. Lower MW PAHs with a bay or bay-like region rapidly dysregulated GJIC in Leydig TM3 cells by relocalization of major testicular gap junctional protein connexin 43 (Cx43) from plasma membrane to cytoplasm. This was associated with colocalization between Cx43 and ubiquitin in intracellular compartments, but without any effect on Cx43 degradation rate or steady-state Cx43 mRNA levels. A longer exposure to active PAHs decreased steady-state levels of full-length Cx43 protein and its 2 N-truncated isoforms. Inhibition of GJIC by PAHs, similarly to a prototypic GJIC-inhibitor TPA, was mediated via the MAP kinase-Erk1/2 and PKC pathways. Polycyclic aromatic hydrocarbon-induced GJIC dysregulation in testes was cell-type-specific because neither PAH dysregulated GJIC in Sertoli TM4 cells, despite PAHs were rapidly taken up by both Leydig TM3 as well as Sertoli TM4 cells. Because TPA effectively dysregulated GJIC in both testicular cell types, a unique regulator of GJIC targeted by PAHs might exist in Leydig TM3 cells. Our results indicate that PAHs could be a potential etiological agent contributing to reproductive dysfunctions in males through an impairment of testicular GJIC and junctional and/or nonjunctional functions of Cx43.
Keywords: Cell Line; signální transdukce; Cell Communication; Phosphorylation; konexin 43; Connexin 43; mužské pohlaví; Signal Transduction; Sertoliho buňky; Mice; polycyklické aromatické uhlovodíky; endokrinní disruptory; Sertoli Cells; Mitogen-Activated Protein Kinases; zátoková oblast polycyklických aromatických uhlovodíků; Endocrine Disruptors; Bay-Region, Polycyclic Aromatic Hydrocarbon; zvířata; Leydigovy buňky; Polycyclic Aromatic Hydrocarbons; viabilita buněk; Cell Survival; mitogenem aktivované proteinkinasy; myši; mezerový spoj; Leydig Cells; buněčné linie; fosforylace; Gap Junctions; mezibuněčná komunikace; Male; Animals